EXPLORING THE IMPACT OF WORK-LIFE BALANCE ON EMPLOYEE ENGAGEMENT IN STARTUP COMPANIES - Pandya, Ami (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Work-life balance has emerged as a crucial determinant of employee well-being, satisfaction, and engagement in the modern workplace. For startup companies—where the pace of work is often intense, resources are limited, and employee roles are fluid—achieving and maintaining a healthy work-life balance becomes both a challenge and a strategic necessity. The significance of work-life balance lies in its capacity to directly influence employee morale, reduce burnout, and foster a culture of trust and loyalty. In recent years, the concept of work-life balance has gained immense relevance, particularly within dynamic and fast-paced organizational settings such as startups. This study seeks to investigate the relationship between work-life balance practices and levels of employee engagement, as perceived by Human Resource (HR) managers working in Ahmedabad-based startup companies. With a sample size of 128 HR managers selected through a random sampling technique, the research utilizes a structured close-ended questionnaire to collect data. The primary objectives of the study are twofold: first, to analyze the perception of HR managers regarding how work-life balance initiatives affect employee engagement, and second, to examine the association between the demographic profiles of HR managers and their perceptions. The findings of the study reveal a strong belief among HR managers that work-life balance initiatives—including flexible working hours and HR policies aligned with employee well-being—significantly contribute to improved employee engagement. These insights underline the growing need for startups to embed work-life balance strategies into their broader human resource practices to foster a more committed, productive, and motivated workforce.